Progress of relationship between cerebral microbleeds and intracranial hemorrhage secondary to cerebral ischemic events - Jie ZHUO (Chinese Journal of Contemporary Neurology and Neurosurgery, 2019)
Cerebral microbleeds (CMBs) are typical neuro-imaging marker of cerebral small vessel disease (cSVD), representing that some small intracranial vessels rupture have occured in the past. Correlation between CMBs and intracranial hemorrhage (ICH) secondary to cerebral ischemic events are currently hot spots in clinical studies among neurologists. There were plenty of Meta-analysis reports on the secondary ICH after CMBs and acute ischemic stroke or transient ischemic attack (TIA) since 2015, and large amounts of patients from multi-centers around the world were included. Because most of these research were based on the Western white race, thus some reports with large-scale east Asian populations (such as China, Japan and Korea patients) were also included as supplement. Overall, there were international consensus that there was significant relation between the incidence rate, number of hemorrhagic focus, spatial distribution of CMBs and secondary ICH post ischemic events, it could be helpful to use CMBs as one of reference indices in risk stratificating and anticoagulation decisions-making. DOI:10.3969/j.issn.1672-6731.2019.09.005